Blues style of Kenny Dorham: harmonic and melodic arrangement of Blue Bossa / Abdul Rahman Zainal Abidin - Zainal Abidin, Abdul Rahman (2022)
This study aims to investigate the improvisation of "Blue Bossa" by Kenny Dorham. Improvising in jazz standard is not easy. It need a lot of knowledge in music theory to improvise effectively just like Kenny Dorham. The purpose of this research is as a contribution of knowledge for other jazz musician who learn to improvise in jazz standards. The objective of this research are to investigate the Blues Style of Kenny Dorham and to investigate the harmonic and melodic arrangement of "Blue Bossa".